Review of the Draft Elements of the Development of the Part 150 Study - Jane Tolmach:::::: (1999)
A statement made by Jane Tolmach discussing the Part 150 Study ant issues that exist within the report. Calls for the rejection of the proposed Master Plan and the revision of the Noise Study.